Use of passive acoustic monitoring to document the distribution of the Indo‐Pacific finless porpoise in the south‐east region of Pearl River estuary, China: Implications for conservation and management. Issue 9 (3rd August 2022) - Fang, Liang; Wang, Xinxing; Li, Min; Chen, Yujian; Wang, Yuezhong; Chen, Tao
Abstract: The Pearl River estuary in Guangdong is home to the Indo‐Pacific humpback dolphin ( Sousa chinensis ) and the Indo‐Pacific finless porpoise ( Neophocaena phocaenoides ). However, limited data are available for the latter species. Line‐transect passive acoustic monitoring surveys were conducted to investigate the distribution of the Indo‐Pacific finless porpoise in the Pearl River estuary in the period July to November 2019. The south‐east region of the Pearl River estuary is an important habitat for the Indo‐Pacific finless porpoise, and more than half of the acoustic detections were within 2 km of islands, concentrated around the uninhabited islands of Soko, Sanmen and Aizhou. The habitat extents of Indo‐Pacific finless porpoises in the survey areas were estimated as 209.04, 761.81 and 976.41 km 2 using 50, 90 and 95% kernel densities, respectively. The 50% kernel density area was mainly around the aforementioned islands and is a priority candidate for protected area status. This is the first report of the distribution and critical habitat of the finless porpoise in the study area. Given the increasing human development in the Pearl River estuary, the results provide important data to help inform the protection of the habitat of finless porpoise in the context of marine planning and development, and promote the establishment of marine protected areas and stronger fisheries management measures.